1964
DOI: 10.1530/acta.0.0460080
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Fluid Volume and Renal Function in Pituitary Insufficiency and Acromegaly

Abstract: Measurement of the volume of extracellular water (ECW) was performed simultaneously with determinations of glomerular filtration rate (GFR) and renal plasma flow (RPF) in 12 hypophysectomized patients (five cases of metastatic mammary carcinoma and seven diabetic subjects) and in 13 cases of acromegaly. Thirteen normal subjects served as controls. ECW was estimated from the volume of distribution of inulin, GFR and RPF from the renal clearances of inulin and para-aminohippurate, respectively. In the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1966
1966
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Many investigators have reported that an increase in extracellular fluid and retention of Na exist in acromegaly [7][8][9][10][11][12][13][14][15], and these were thought to contribute to hypertension. In addition, the increase in extracellular fluid was reduced after treatment of the disease [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have reported that an increase in extracellular fluid and retention of Na exist in acromegaly [7][8][9][10][11][12][13][14][15], and these were thought to contribute to hypertension. In addition, the increase in extracellular fluid was reduced after treatment of the disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…Quite interestingly, a high incidence of hypertension has been noticed in patients with acromegaly [2][3][4][5][6]. It has been reported that plasma volume and serum Na are increased in acromegaly [7][8][9][10][11][12][13][14][15], and these are able to induce hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[11] may, as suggested by Mogensen and Andersen [2], contribute to the kidney enlargement. Acromegalic patients have increased growth hormone, kidney size, GFR and RPF [12].…”
Section: Discussionmentioning
confidence: 99%
“…2 Hynson, Westcott and Dunning, Baltimore, Md. 3 Cutter Laboratories, Berkeley, Calif. R. PREISIG, T. 0. MORRIS, 1.…”
Section: Methodsmentioning
confidence: 99%